The mechanisms and treatments for sarcopenia: could exosomes be a perspective research strategy in the future?. Issue 2 (27th January 2020) - Rong, Shuang; Wang, Liangliang; Peng, Zhao; Liao, Yuxiao; Li, Dan; Yang, Xuefeng; Nuessler, Andreas K.; Liu, Liegang; Bao, Wei; Yang, Wei
Abstract: The age‐related loss of muscle mass and muscle function known as sarcopenia is a primary contributor to the problems faced by the old people. Sarcopenia has been a major public health problem with high prevalence in many countries. The related underlying molecular mechanisms of sarcopenia are not completely understood. This review is focused on the potential mechanisms and current research strategies for sarcopenia with the aim of facilitating the recognition and treatment of age‐related sarcopenia. Previous studies suggested that protein synthesis and degradation, autophagy, impaired satellite cell activation, mitochondria dysfunction, and other factors associated with muscle weakness and muscle degeneration may be potential molecular pathophysiology of sarcopenia. Importantly, we also prospectively highlight that exosomes (small vesicles) as carriers can regulate muscle regeneration and protein synthesis according to recent researches. Dietary strategies and exercise represent the interventions that can also alleviate the progression of sarcopenia. At last, building on recent studies pointing to exosomes with the roles in increasing muscle regeneration, mediating the beneficial effects of exercise, and serving as messengers of intercellular communication and as carriers for research strategies of many diseases, we propose that exosomes could be a potential research direction or strategies of sarcopenia in the future.